Challenges of Using Information and Communication Technology in Teaching English in Nepal - Paudel, Pitambar (KMC Journal, 2022)
Nepal government has initiated the policy of integrating Information and Communication Technology (ICT) at school level education with the hope of empowering quality in education by enhancing teachers’ and students’ knowledge, confidence and skills in ICT use. In this scenario, this study aimed to investigate the challenges in implementing ICTs in language education from teachers’ perspectives. For this objective, sequential explanatory mixed method research design was used. Questionnaire, interview and observation were the tools used for data collection from 40 purposively selected secondary level English teachers. Quantitative data were analyzed statistically while qualitative information was analyzed textually. Both the results were integrated and interpreted in discussion. The findings exhibited that teacher and policy-related obstacles were the significant challenges than institution/school-related ones. The findings indicate that teachers are in need of immediate training on ICT use in language teaching to enhance their professionalism in ICTs and adequate ICT policy should be implemented to achieve optimum opportunities and reduce the challenges.